Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Gudang PT J&T Express di Semarang - Ihda Nor Rohmah; Teti Safari; Hesti Ristanto; Riyono Riyono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of work environment and job satisfaction on the performance of warehouse employees at PT J&T Express. Work environment and job satisfaction are important factors that are thought to increase productivity and work efficiency. The research method used is quantitative with a survey approach, data collection through questionnaires announced to 100 warehouse employees of PT J&T Express using a purposive sampling technique. The data obtained were analyzed using linear multiple regression to test the partial and simultaneous effects of independent variables on the dependent variable. The results of the study indicate that work environment and job satisfaction have a significant positive effect on the performance of warehouse employees. This finding indicates that improving the quality of the work environment and job satisfaction can be an effective strategy in improving employee performance at PT J&T Express. This study is expected to provide practical contributions to company management in managing human resources to increase company competitiveness.